PW 0426 Incidence and characteristics of unintentional injuries among children in a resource limited setting in kampala, uganda. (November 2018) - Ssemugabo, Charles; Mukama, Trasias; Halage, Abdullah Ali; Paichadze, Nino; Gibson, Dustin; Kobusingye, Olive
Abstract : Introduction: Childhood unintentional injuries remain understudied. This assessed the incidence and characteristics of all unintentional injuries among children aged 18 years and below in a slum community in Uganda. Methods: A cross-sectional survey was conducted among households in a slum community using a semi-structured interviewer-administered questionnaire. Incidence of unintentional injuries in children<18 years old was calculated. Crude and adjusted logistic regressions were conducted to obtain odds ratios and 95% CI for factors associated with injury characteristics by sex and age categories Results: Out of 1583 children in the 422 surveyed households, 44.6% (706/1583) had suffered from at least one unintentional injury yielding an annual incidence rate of 446 per 1000 children. Cuts, animal bites or open wounds 30.6% (185/608), and bruises or superficial injuries 28.6% (174/608) were the commonest injuries. Majority of injuries occurred at home, 75.5% (459/608). Falls 56.7% (345/608) and playing or recreation 83.6% (508/608) were the leading cause and activity at time of injury respectively. Boys were significantly more likely to be injured at school (AOR 4.34; 95% CI 1.22–15.54) and to be injured from falls (AOR 1.41; 95% CI 1.01–1.96), as compared to girls. Older children (12–18 years) were more likely to suffer from fractures (AOR 2.37; 95% CI 1.26–4.43) concussions and organ system injuries (AOR 3.58; 95% CI 1.–3 – 12.39) and cuts, bites or open wounds (AOR 2.05; 95% CI 1.21–3.48) as compared to younger children. Older children were less likely to have burns or scalds as compared to the youngest children (AOR: 0.23; 95% CI 0.11 to 0.50). Conclusions: Unintentional injury incidence rate was high among children with most occurring in the homes. Injury prevention interventions should aim at creating safe playing spaces for children and developing awareness programs about injury prevention.